KEBIJAKAN PELAKSANAAN PROGRAM DANA PENSIUN LEMBAGA KEUANGAN (DPLK) INDIVIDU PADA PT. BANK BJB, TBK. KANTOR CABANG PEMBANTU PAMULANG - Tatyana Tatyana; Ni Luh Padmi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
The Individual Financial Institution Pension Fund (DPLK) is one of the programs established by the Bank as a financial institution to improve the welfare of participants at retirement age. Welfare insurance at retirement age is very important to anticipate the risks that will arise during the participant's life journey. The existence of this welfare guarantee allows employees to minimize problems that arise from the risks that will be faced in the course of their lives, such as the risk of losing their job, getting old, accidents resulting in disability, or even death. Bank BJB KCP Pamulang in this case provides banking services and services, one of which is Individual DPLK. Individual Financial Institution Pension Fund (DPLK) is a pension fund established by a bank or life insurance to organize a Defined Contribution Pension Program (PPIP) for individuals, both employees and independent workers. Bank BJB organizes individual DPLK Programs to help to create a prosperous future through early retirement planning